PENGARUH MOTIVASI KERJA, KEPEMIMPINAN DAN BUDAYA SEKOLAH TERHADAP KINERJA DENGAN MEDIASI KEPUASAN (Studi pada guru SMP Negeri Kecamatan Margorejo di Kabupaten Pati) - Sunanto, Sunanto (Students Journal of Economic and Management, 2012)
This study aims to examine and analyze the effect of work motivation, leadership of the principal and school culture of teacher performance by mediation of job satisfaction of Yunior High School Teacherin the district Margorejo Pati. The research was conducted by the method of census conducted on 82Â  junior high school teachers in the District Margorejo Pati. Region research techniques are used to fill in a questionnaire given to the respondents.Mechanical testing data used in this study include test validity with factor analysis, the Cronbach alpha reliability test, double regression analysis, t test, Determination test, normality tes and assumstion classic test covering multicolonieritas, heteroscedasticity. The results of the analysis and discussion of this study show that: work motivation has positive and significant impact on job satisfaction, leadership principal has no effect on job satisfaction, school culture has positive and significant impact on job satisfaction, work motivation no effect on the performance of teachers, principal leadership positive and significant impact on teacher performance, and school culture had no effect on teacher performance. The mediating effect on work motivationÂ  affect performance mediated job satisfaction, mediation of principal leadership affects the performance of teachers directl but the principalâs leadership on the teacher performance is not mediated by job satisfaction. Keywords: Work Motivation, Principal Leadership, School Culture, Job Satisfaction and Performance.